Constructing two-scale network microstructure with nano-Ti5Si3 for superhigh creep resistance. Issue 8 (August 2019) - Jiao, Y.; Huang, L.J.; Wei, S.L.; Peng, H.X.; An, Q.; Jiang, S.; Geng, L.
Graphical abstract: Highlights: The two-scale network microstructure with nano-Ti5 Si3 was constructed. The rupture time of composite can be increased by 20 times. Nano-Ti5 Si3 which dissolved to smaller one can further enhance creep resistance. The two-scale network microstructure can block grain and phase boundary sliding. Abstract: The improvement of mechanical properties must be achieved by designing and constructing more suitable microstructure, such as hierarchical microstructure. In order to significantly enhance the creep resistance of titanium matrix composites (TMCs), two-scale network microstructure was constructed including the first-scale network (<150 μm) with micro-TiB whisker (TiBw) reinforcement and the second-scale network (<30 μm) with nano-Ti5 Si3 reinforcement by powder metallurgy and in-situ synthesis. The results showed that the creep rate of the composite was remarkably reduced by an order of magnitude compared with the Ti6Al4V alloy at 550 °C, 600 °C, 650 °C under the stresses between 100 MPa and 350 MPa. Moreover, the rupture time of the composite was increased by 20 times, compared with that of the Ti6Al4V alloy at 550 °C/300 MPa. The superior creep resistance could be attributed to the hierarchical microstructure. The micro-TiBw reinforcement in the first-scale network boundary contributed to creep resistance primarily by blocking grain boundary sliding, while the nano-Ti5 Si3 particle in the second-scale network boundary mainly by hindering phase boundary sliding. In addition, the nano-Ti5 Si3 particle was dissolved, and precipitated with smaller size than the primary Ti5 Si3 . This phenomenon was attributed to Si element diffusion under high temperature and external stress, which could further continuously enhance the creep resistance. Finally, the creep rate during steady-state stage was significantly decreased, which manifested superior creep resistance of the composite.